Noninvasive hemodynamic assessment of type 2 diabetes mellitus using four-dimensional flow magnetic resonance imaging - Di Wu; Jiachen Ji; Yuancheng Wang; Shujun Zhang; Hong Ge; Mingzhu Fu; Yunduo Li; Shenghong Ju; Rui Li (EngMedicine)
Background: Noninvasive and early evaluation of hemodynamic conditions in patients with type 2 diabetes mellitus (T2DM) and diabetic nephropathy (DN) is crucial for assessing disease progression. This study aimed to investigate early hemodynamic changes in patients with T2DM and evaluated the efficacy of Four-Dimensional Flow Magnetic Resonance Imaging (4D Flow MRI) in detecting and diagnosing T2DM and DN. Methods: The abdominal 4D Flow MRI data from 23 patients with T2DM and 23 healthy volunteers were collected and validated for subsequent analysis. The data were preprocessed, and blood flow visualization and quantitative hemodynamic measurements in the renal and splenic arteries were performed by experienced reviewers. The key parameters measured included the average velocity (Vavg), the net volume of blood flow in one cardiac cycle (Flowcyc), and the resistance index (RI). The reproducibility of these measurements was assessed with Bland-Altman analysis, differences between groups were evaluated using t-tests, and their diagnostic utility for T2DM and DN was analyzed using ROC curves. Results: This study confirmed the high reproducibility of 4D Flow MRI for measuring Vavg and Flowcyc, with the RI showing higher variability. T2DM patients exhibited significantly lower flow and higher resistance in the renal and splenic arteries than controls, indicating vascular changes. Receiver operating characteristic (ROC) analysis highlighted the diagnostic accuracy of specific hemodynamic parameters, with right renal artery RI and left renal artery flow being particularly effective for diagnosing T2DM and DN, respectively. Conclusions: 4D Flow MRI could be a noninvasive and quantitative method to comprehensively depict hemodynamics and a possible evaluation method for T2DM and DN.